2018
DOI: 10.1098/rstb.2017.0205
|View full text |Cite
|
Sign up to set email alerts
|

How mammals stay healthy in nature: the evolution of behaviours to avoid parasites and pathogens

Abstract: Mammals live and thrive in environments presenting ongoing threats from parasites in the form of biting flies, ticks and intestinal worms and from pathogens as wound contaminants and agents of infectious disease. Several strategies have evolved that enable animals to deal with parasites and pathogens, including eliminating away from the sleeping–resting areas, use of an array of grooming techniques, use of saliva in licking, and consuming medicinal plant-based compounds. These strategies all are species-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 73 publications
0
85
0
1
Order By: Relevance
“…Several strategies have evolved that enable wild mammals to deal with parasites. These include eliminating infectious agents from sleeping/resting areas, having an array of grooming techniques, consuming medicinal plant-based compounds, and others (Hart and Hart 2018). These strategies are speciesspecific and reflect particular environments that animals inhabit.…”
Section: Behavior and Socialitymentioning
confidence: 99%
“…Several strategies have evolved that enable wild mammals to deal with parasites. These include eliminating infectious agents from sleeping/resting areas, having an array of grooming techniques, consuming medicinal plant-based compounds, and others (Hart and Hart 2018). These strategies are speciesspecific and reflect particular environments that animals inhabit.…”
Section: Behavior and Socialitymentioning
confidence: 99%
“…Evidence for this pattern is however missing. In addition, individuals may learn to recognize and avoid infected individuals -as in mandrills which can recognize the smell of individuals infected by protozoan parasites, and avoid grooming them (Poirotte et al, 2017; see also reviews on parasite avoidance behaviors: Hart and Hart, 2018;Kavaliers and Choleris, 2018;Sarabian et al, 2018). Hosts can also learn to avoid contact with pathogens -as in the Nematode Caenorhabditis elegans that learns to associate the smell of a pathogenic bacteria with a hazard (Zhang et al, 2005).…”
Section: Mechanism 12: Cognitive Abilities Help To Avoid or Respondmentioning
confidence: 99%
“…Allogrooming is widespread across the animal kingdom [i.e., primates (Lehmann et al, 2007), birds (Bush and Clayton, 2018), ungulates (Hart and Hart, 2018), and insects (Octavio Lopez-Riquelme and Luisa Fanjul-Moles, 2013)]. This includes removing ectoparasites with hands (Lehmann et al, 2007), bills (Bush and Clayton, 2018), teeth (Hart and Hart, 2018), or mouthparts (Octavio Lopez-Riquelme and Luisa Fanjul-Moles, 2013). Although many species appear to tolerate some ectoparasites (Hart, 2011), they may also be vectors of other diseases (Sadanandane et al, 2018), making their removal beneficial for both the parasitized individual and the wider social group.…”
Section: Groomingmentioning
confidence: 99%
“…Analyses of grooming patterns have shown that for many species, grooming is a key mechanism for establishing and maintaining relationships with kin, allies, or mates and maintaining group cohesion (Lehmann et al, 2007). However, it also serves important hygienic functions (Hart and Hart, 2018). While most animals can self-groom, social grooming is particularly important for areas of the body which the animal cannot reach (Hart and Hart, 2018).…”
Section: Groomingmentioning
confidence: 99%